Obesity Does Not Increase Operative Time in Otologic Surgery: An Analysis of 5125 Cases. Issue 2 (February 2018) - Muelleman, Thomas; Shew, Matthew; Muelleman, Robert J.; Villwock, Mark; Sykes, Kevin; Staecker, Hinrich; Lin, James
Abstract : Objectives: A large shoulder can impact otologic surgical access. The physical obstruction of a large shoulder may force the surgeon to adjust his or her posture or hand position. We sought to assess the effect of body mass index (BMI) on operative time in tympanoplasties and tympanomastoidectomies. Study Design: Cross-sectional analysis. Setting: National surgical quality improvement program dataset (NSQIP) 2011 to 2014. Patients: Current procedural terminology (CPT) codes were used to identify patients undergoing tympanoplasties and tympanomastoidectomies. Interventions: Otologic surgery as indicated by CPT code. Main Outcome Measures: Targeted variables included height, weight, and operative time. BMI was stratified to assess a range of body compositions (<25, 25–30, >30–35, >35–40, >40). Categorical variables were compared using χ 2 tests and continuous variables were compared using Kruskal–Wallis tests. Correlation between operative time and BMI was assessed using Spearman's rho. A generalized linear model was used to analyze the variables affecting operative time. Surgical complications were assessed in binary logistic regression using the enter method. Two-tailed significance was set at α = 0.05. Results: Two surgical groups were identified: tympanoplasty (n = 3, 508) and tympanomastoidectomy (n = 1, 617). There was not a significant difference in mean operative time across the BMI subgroups for either surgical group ( p = 0.617, 0.859, respectively). Multivariate analyses showed no significant difference in operative times based on BMI classification. Conclusions: The body habitus of obese patients may force the otologic surgeon to adapt, but obese patients do not have a statistically significant longer mean operative time for tympanoplasties and tympanomastoidectomies than patients with a lower BMI. Abstract : Supplemental Digital Content is available in the text